2006
DOI: 10.5642/aliso.20062201.02
|View full text |Cite
|
Sign up to set email alerts
|

Robust Inference of Monocot Deep Phylogeny Using an Expanded Multigene Plastid Data Set

Abstract: We use multiple photosynthetic, chlororespiratory, and plastid translation apparatus loci and their associated noncoding regions (ca. 16 kb per taxon, prior to alignment) to make strongly supported inferences of the deep internal branches of monocot phylogeny. Most monocot relationships are robust (an average of ca. 91 % bootstrap support per branch examined), including those poorly supported or unresolved in other studies. Our data strongly support a sister-group relationship between Asparagales and the comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
127
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 75 publications
20
127
3
1
Order By: Relevance
“…By contrast, the insufficiently resolved rbcL tree placed Flagellaria, Anarthriaceae and (JEP families + Restionaceae including Centrolepidaceae) at a trichotomy, a position for Flagellaria more in agreement with the results from combined data of morphology, atpA and rbcL (Michelangeli et al 2003). Graham et al (2006) and found Flagellaria to be sister to a clade including both Poaceae and Restionaceae. Data from rbcL, matK and trnL-F relevant to relationships within the restiid clade will be presented elsewhere.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…By contrast, the insufficiently resolved rbcL tree placed Flagellaria, Anarthriaceae and (JEP families + Restionaceae including Centrolepidaceae) at a trichotomy, a position for Flagellaria more in agreement with the results from combined data of morphology, atpA and rbcL (Michelangeli et al 2003). Graham et al (2006) and found Flagellaria to be sister to a clade including both Poaceae and Restionaceae. Data from rbcL, matK and trnL-F relevant to relationships within the restiid clade will be presented elsewhere.…”
Section: Discussionsupporting
confidence: 81%
“…strict. by Briggs et al (2000), Bremer (2002), Michelangeli et al (2003), Chase et al (2006) and Graham et al (2006). In particular, strongly supported clades here are (Poaceae, Ecdeiocoleaceae, Joinvilleaceae) and (Restionaceae, Centrolepidaceae).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…2). McPherson et al (submitted) found strong bootstrap support for a sister relationship of lxioliriaceae and Tecophilaeaceae with molecular data; however, they did not sample Doryanthaceae (but see Graham et al 2006). Analyses of morphological data and base chromosome number support the sister relationship of Ixioliriaceae and Tecophilaeaceae (Stevenson and Loconte 1995) and place Doryanthes as sister to lridaceae (Rudall 2002b).…”
Section: Phylogeny and Morphological Evolution Of Asparagalesmentioning
confidence: 95%
“…However, there is no doubt that Agavaceae belong to the "higher core Asparagales", together with Hyacinthaceae, Asparagaceae and Ruscaceae (see below, (6)) as well as further families without succulents. In a radical approach, all these families are treated as a much enlarged family Asparagaceae (APG 2003(APG , 2009Graham et al, 2006), circumscribed by racemose inflorescences (in comparison with the umbellate inflorescences of the "lower core Asparagales", but with numerous exceptions) (see below, (3)). …”
Section: No Tes O N Selec Ted Familiesmentioning
confidence: 99%